Does a patient with cardiac disease after a sudden cardiac arrest require education? - Kamińska, Martyna; Krzemińska, Sylwia Anna (Journal of Education, Health and Sport, 2018)
Introduction: Health education in a holistic approach consists in motivating and stimulating the sick and healthy people to learn to strengthen their own health, responsibility for their own health and shaping a healthy lifestyle. Contemporary education is focused on self-observation and self-care, these are the basic forms of health care. In everyday life, people undertake activities that strengthen the pursuit of health through: lifestyle, avoiding life-threatening situations, comfort in the biopsychosocial area, the use of therapeutic methods and rehabilitation. Sudden cardiac arrest is a condition which directly threatens life, and there is a cessation of cardiac mechanical activity. This Life-threatening condition occurs when one ceases to function properly with the systems responsible for maintaining vital functions.Aim .: Presenting the role of nurses in the care of patients after cardiac arrest in the course of myocardial infarction and the need for education to prevent recurring health risks.Material and method: The method applied was that case study.Conclusions: The main problem of the patient after cardiac arrest were as follows- the possibility of re-cardiac arrest, shortness of breath, discomfort due to immobilization, depressed mood. During the nursing actions should eliminate the factors influencing the development of complications that can lead to death. The role of nurses is patient education aimed at improving the quality of life and reduce the risk of recurrence of cardiac arrest. Nursing care of the patient after cardiac arrest requires nurses to constantly extend knowledge, excellence and knowledge of the latest guidelines. Sudden cardiac arrest is a major challenge for modern medicine and should increase the scope of research on this issue